Closing the evidence gap in infectious disease: point-of-care randomization and informed consent. (February 2017) - Huttner, A.; Leibovici, L.; Theuretzbacher, U.; Huttner, B.; Paul, M.
Abstract: The informed consent document is intended to provide basic rights to patients but often fails to do so. Patients' autonomy may be diminished by virtue of their illness; evidence shows that even patients who appear to be ideal candidates for understanding and granting informed consent rarely are, particularly those with acute infections. We argue that for low-risk trials whose purpose is to evaluate nonexperimental therapies or other measures towards which the medical community is in a state of equipoise, ethics committees should play a more active role in a more standardized fashion. Patients in the clinic are continually subject to spontaneous 'pseudo-randomizations' based on local dogma and the anecdotal experience of their physicians. Stronger ethics oversight would allow point-of-care trials to structure these spontaneous randomizations, using widely available informatics tools, in combination with opt-out informed consent where deemed appropriate.